Factors that Influence Accounting Students to Choose Accounting Majors at University in Medan - Vina Arnita; Suwarno Suwarno; Fitri Hasanah (JFBA: Journal of Financial and Behavioural Accounting, 2021)
The research aims to empirically prove the effect of education costs, interests and motivation on the choice of accounting major. This research was conducted on accounting students at Universitas Pembangunan Panca Budi, Medan. This research uses quantitative associative research. The data analysis technique used is the classical assumption test, multiple linear regression test, and the coefficient of determination (Adjusted R Square). The basis for sampling in this study used a saturated sample (census) with a total sample of 300 respondents. The results of this study indicate that partially the cost of education, interest and motivation have a significant effect on the selection of accounting majors. This can be seen in the results of the coefficient of determination (Adjusted R Square) which means that the variability of the dependent variable that can be explained by the independent variable is 65.3% %. While the remaining 34.7% is explained by other variables that are not included in the regression model.